Early oxidation mechanism of austenitic stainless steel TP347H in supercritical water. (November 2017) - Li, Yanhui; Wang, Shuzhong; Sun, Panpan; Xu, Donghai; Ren, Mengmeng; Guo, Yang; Lin, Guike
Graphical abstract: Highlights: Early forming mechanism of scales on typical austenitic steels in SCW. Three oxidation stages: rapid, transitory stage, and diffusion-controlled. Formation priority of continuous inner Cr-rich layer relative to outer layer. The Cr 6+ species (likely CrO2 (OH)2 ) only occurred in the very early phase. Relative constant content of hydroxides on sample surface. Abstract: The initial corrosion behaviour of austenitic TP347H exposed to supercritical water was investigated. The early oxidation can be categorized into three stages (rapid oxidation, transitory, and diffusion-controlled stages). Higher temperature resulted in a transformation towards the subsequent stage earlier and less oxidation resistance. Cr 6+ species (likely CrO2 (OH)2 ) were only generated on the surface in the very early phase, and then they gradually disappeared as the exposure time increased. Compared with a complete outer Fe-rich oxide layer, the formation priority of a continuous inner Cr-rich layer was observed at 540 °C within 35 h. A corresponding early oxidation process was determined.